FACTORS INFLUENCING COMPETENCY DEVELOPMENT OF NURSES AS PERCEIVED BY STAKEHOLDERS IN VIETNAM - Do Thi Ha; Khanitta Nuntaboot (Belitung Raya Foundation, Indonesia, 2020)
Background: Competency of nurses is vital to safe nursing practice as well as essential component to drive quality of nursing services. Competency development is a continuous process of improving knowledge, attitudes and skills, and is influenced by a numerous of factors. Purposes: This study aims to explore factors that influence the development of competencies of nurses working in clinical settings in Vietnam. Methods: A descriptive qualitative research was conducted in Ho Chi Minh City, Vietnam with a purposive sample of twenty-seven participants including nurses, nurse managers, administrators, nurse teachers, medical doctors, and other health care providers. Data collection was by in-depth interviews and focus group discussions. Content analysis was used to analyze the data. Findings: The research participants described numerous of factors that influence the journey of developing nurses’ competencies. The identified factors were relevant to nursing education and training system in Vietnam; working environments of nurses; public image and values of nursing profession; characteristics of nurses themselves; Vietnamese nursing profession; sociocultural-economic and political aspects in Vietnam; and global contexts. Conclusion: The derived knowledge would greatly benefit clinical nurses, administrators, nursing educators, health care services managers, policy makers as well as other relevant health care stakeholders in proposing of solutions to promote nursing education, nursing workplace environments, and the appropriate regulations in order to enhance the nursing competency and quality of nursing services in Vietnam.